Emotional experiences and identity construction of pre-service English teachers during teaching practicum in Indonesia - Pravitasari, Hikmah; Yanto, Elih Sutisna; Fatihah, Ila Nur Kholis (English Education Department, Universitas Islam Indonesia, 2025)
This study explored pre-service English teachers’ emotional experiences and professional identity construction during their teaching practicum in Indonesia. Using a qualitative approach, narrative inquiry was employed to gather data from two pre-service teachers through semi-structured interviews and reflective diaries. Thematic analysis was conducted to identify themes related to their emotional experiences, such as anxiety, self-doubt, and motivation, and how these emotions influenced their teacher identities. Findings revealed that positive emotions like enthusiasm and empathy facilitated professional identity formation, while negative emotions such as anxiety and fear of making mistakes posed challenges. Mentor teachers played a crucial role in both alleviating and exacerbating these emotional responses. The study highlights the importance of emotional management and identity development in teacher preparation programs. However, the study’s limitation lies in its small sample size, focusing on two participants from a private university in Indonesia. Future research could expand the sample size and explore the emotional dynamics of pre-service teachers in different contexts or academic fields.